Unravelling Gender Inequality: A Semiotic Analysis of Taylor Swift's Song Lyrics - Wildania Fadila; Baiatun Nisa (Globish: An English-Indonesian Journal for English, Education, and Culture, 2024)
This study aims to explore the semiotic representations of gender inequality within Taylor Swift's song lyrics. Utilizing a descriptive qualitative method, it analyzes the signifier and signified embedded in her music. Drawing upon Ferdinand de Saussure's semiotic theory, the study delves into the material aspects of languageâ€”what is seen, heard, or read (signifier)â€”and the corresponding mental images or concepts (signified). Through a comprehensive analysis of Swift's songs, including "The Man," "Mad Woman," and "Look What You Made Me Do," the research uncovers the pervasive gender gap and mistreatment faced by women in various societal contexts. Data collection involves listening to the songs, understanding their meaning, and observing instances of discrimination against women in daily life. The findings highlight the significance of Swift's music as a platform for discourse on gender inequality, shedding light on the ongoing struggle for women's rights in contemporary society.Â